STRATEGI ADAPTIF BANK PERKREDITAN RAKYAT DALAM MENGHADAPI EKSPANSI KREDIT UMKM BANK UMUM DI MALANG - Sari Yuniarti (Jurnal Keuangan dan Perbankan, 2011)
The competition of giving credit small and medium enterprises (SMEs) was tighter. After global finance crisis, private banks and BUMN banks fought for living fund to customers. This activity was done by BPR. For this reason, BPR had to have an adaptive strategy to adapt to the changes happened, which was considered unbeneficial because there was an expansion public banks which offered SMEs credit. This research aimed at knowing how adaptive strategy done by BPR in facing credit expansion of SMEs done by public banks in Malang. The data used was primary data taken from questionnaire and interview to BPR. By using qualitative descriptive analysis technique, it could be known that BPR needed giving protection through guarantee pattern so that it could develop SMEs to become feasible and bankable SMEs, strengthen BPR industry infrastructure, strengthen network inter micro finance institution and between BPR and LKM, and establish a mutual and solid partnership which became the strong point of BPR compared with public banks.